Computational fluid dynamical analysis of turbulent flow in a channel equipped with double-pass solar air collector - Saim, Rachid; Abderrahim, Asma; Öztop, Hakan Fehmi; Abbdoui, Said; Al-Salem, Khaled (Inderscience Enterprises Ltd, 2015)
A numerical analysis is proposed to predict the thermal and flow field for turbulent flow in a double-pass solar collector. The conservation equations are solved by using finite volume method. The k-omega-SST turbulence model is used. The influence of the mass flow rate of air, which changes in range of 0.0139 kg/s and 0.062 kg/s, is chosen as the main parameter. The results show that the flow characteristics strongly depend on massflow rate of air and the geometry of the double pass solar air collector.
Keywords: double pass solar air collector; forced convection; turbulent flow; numeric